Fecal urgency: a key symptom in patients with inflammatory bowel disease - Carvajal, Francisca (2026)
Fecal urgency (FU) is a common symptom in patients with inflammatory bowel disease (IBD), associated with a significant deterioration in quality of life (QoL) and clinical complications. However, it is often omitted as a parameter in classic disease activity indices. Objective: To evaluate the prevalence of FU and its relationship with inflammatory activity, fecal calprotectin, and QoL in patients with IBD. Materials and methods: Analytical, crosssectional study in 268 patients treated between March and July 2023 in three centers in Santiago. Sociodemographic, clinical, and biomarker information was collected, evaluating QoL using the IBDQ-32 questionnaire and Patient-reported outcome using the IBD-Control 8 scale. Kruskal-Wallis and chi-square tests were applied for statistical analysis (p<0.05). Results: The prevalence of FU was 20%, being moderate-severe in one third of the cases. In patients with ulcerative colitis, 59% of those with UF were in symptomatic remission versus 98% without UF (p<0.001). In Crohn's disease, 74% with UF were in remission versus 100% without UF (p<0.001). Furthermore, patients with UF presented higher levels of FC and a significant deterioration in QoL (p<0.001). Conclusions: These findings highlight the need to include UF as a relevant parameter in the evaluation and management of IBD, given its impact on inflammatory activity and deterioration in QoL. Incorporating it could improve the comprehensive care of patients and optimize therapeutic strategies.